Transient analysis of laminated composite shallow shell by using new higher order shear deformation theory - Ghazi Kareem, Marwa; Widad I. Majeed, Dr. (International Journal of Engineering and Technology, 2019)
The present work is a transient discussion that based on the recent higher position of the shear deformation function proposed by J.L. Mantari et al [Composite Structures 94 (2011) 37–49] who develops the idea behind the supported cross-ply laminated shallow shell. It explains the recent hint of displacement which based on a parameter ‘‘m’’, when its worth is optimized in order to get closest outcomes of the elasticity of the 3D solutions. The transient solutions are obtained using Navier series for thick and thin anti-symmetric and symmetric cross ply laminated shallow shell. Results are provided for several designed parameters like the quantity of laminates, curvature ratio and the ratio of the thickness on the laminated combined dynamic behavior (Glass/epoxy) and hybrid (Glass/carbon/epoxy) shallow shell subjected to sinusoidal distributed load and uniformly distributed load with different types of time dependent loading such as sine pulse, triangular pulse and step pulse are studied. The accuracy of the present codes by using Matlab R2017b is verified by comparing with other works solution and Ansys 15 software.